Finite element model updating of multi-span greenhouses based on ambient vibration measurements. (September 2017) - Ha, Taehyu; Kim, Jinwon; Cho, Bong-Ho; Kim, Dae-Jin; Jung, Ji-Eun; Shin, Seung-Hoon; Kim, Hongjin
Abstract : Plastic greenhouses are often designed with low levels of safety. As a result there has been an increasing number of structural failures due to abnormal climatic conditions such as heavy snow and strong winds. Standardised prototypes are often used to facilitate the design process, but these prototypes cannot withstand every extreme loading condition. To aid the accurate evaluation of the disaster resilience of plastic greenhouse structures, finite element (FE) analysis for specific load cases is essential in their design process. In plastic greenhouses, clamp connectors and swivel couplers are generally used to connect beams to columns and arched rafters to purlins, and columns are usually driven directly into the ground to support the entire structure. In the FE analysis, however, connections and supports are idealised as fully rigid or frictionless-pinned, which does not accurately reflect realistic conditions. In this study, ambient vibration tests were performed on two full-scale models to identify the dynamic properties of multi-span greenhouses. FE model updating was then carried out to determine the rigidity factors of connections and supports that yield the same dynamic properties as built structures. The results showed that the modelling of connections and supports causes significant changes in modal frequencies. They also showed that the connection modelling condition contributed more to the dynamic parameters of the multi-span greenhouses than the support modelling condition. Highlights: Ambient vibration tests were performed on two full-scale multi-span greenhouses. Two output-only system identification methods were adopted. FE model updating was performed to determine the rigidity factors of analysis model.